Human sperm chaperone HSPA2 distribution during in vitro capacitation. (February 2021) - Huerta-Retamal, Natalia; Sáez-Espinosa, Paula; Robles-Gómez, Laura; Avilés, Manuel; Romero, Alejandro; Aizpurua, Jon; Gómez-Torres, María José
Highlights: Sperm capacitation changes need longer time than the suggested by WHO guidelines. Capacitation-associated plasma membrane remodelling includes HSPA2 modifications. HSPA2 must be at the equatorial band and acrosomal region during gamete interaction. HSPA2 may be a good biomarker of capacitation and sperm maturity. Abstract: Human fertilization success depends on the ability of the spermatozoa to undergo capacitation. Even though this process can be conducted in vitro, the optimal time for a sperm cell to complete capacitation in vitro is still under discussion due to the lack of proper capacitation biomarkers. Here, we evaluated the influence of in vitro capacitation time on HSPA2 distribution over human sperm head testing this chaperone as a potential capacitation biomarker. The chaperone was assessed in human spermatozoa from 16 normozoospermic donors using indirect immunofluorescence in uncapacitated, one and four-hour capacitated spermatozoa. The percentage of HSPA2 immunofluorescent cells before and after one hour of capacitation did not differ significantly. However, after four hours of capacitation, we observed a significantly higher percentage of HSPA2 labelled cells. In fluorescent cells analysed before capacitation, we could not identify a predominant distribution pattern. Meanwhile, after capacitation, most sperm showed a highly labelled equatorial band accompanied by a homogeneous fluorescence throughout the acrosomal region. Our findings suggest that HSPA2 needs more than one hour of in vitro capacitation for being correctly distributed in the anterior region of the sperm head. In conclusion, the present study provides solid evidences for the utility of HSPA2 as a biomarker of human sperm in vitro capacitation. Due to its importance during egg-sperm recognition, the use of HSPA2 as a biomarker before an artificial reproduction technique may be suggested, in addition to a longer capacitation time during sperm preparation.